New Media as an Ideological Transmission Opportunity for Religious Authorities in Indonesia - Ronaldi, Abon; Saidek, Abdul Rahim; Lestari, Wiji (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2023)
This paper endeavors to explore the impact of New Media on the dynamics of religious authorities, with a particular focus on Indonesia. Seeking to challenge the prevailing assumption, this research adopts a qualitative method grounded in a comprehensive literature review. Drawing from diverse sources such as journal articles, proceedings, books, and online news, the study poses a pivotal question: how do religious authorities in Indonesia leverage New Media as a conduit for ideological transmission? In contrast to the commonly held belief, the proposed thesis of this article contends that New Media doesn't serve as a catalyst for the transformation of religious authorities in Indonesia. Instead, it functions as a valuable opportunity for the dissemination of religious information. Framed within the media technology perspective articulated by Gill Branston and Roy Stafford (2003), the findings of this research underscore the strategic design of platforms like the Nahdlatul Ulama Online website, the Indonesian Ulema Council Da'wah Application, and Muhammadiyah.or.id to illustrate that New Media serves as a potent tool for Indonesian Islamic authorities in fortifying the organizational identity.